Biomarkers of oxidative stress in urine and plasma of operators at six Singapore printing centers and their association with several metrics of printer-emitted nanoparticle exposures. Issue 9 (26th November 2022) - Bello, Dhimiter; Chanetsa, Lucia; Christophi, Costas A.; Singh, Dilpreet; Setyawati, Magdiel Inggrid; Christiani, David C.; Chotirmall, Sanjay H.; Ng, Kee Woei; Demokritou, Philip
Abstract: Inhalation of nanoparticles emitted from toner-based printing equipment (TPE), such as laser printers and photocopiers, also known as PEPs, has been associated with systemic inflammation, hypertension, cardiovascular disease, respiratory disorders, and genotoxicity. Global serum metabolomics analysis in 19 healthy TPE operators found 52 dysregulated biomolecules involved in upregulation of inflammation, immune, and antioxidant responses and downregulation of cellular energetics and cell proliferation. Here, we build on the metabolomics study by investigating the association of a panel of nine urinary OS biomarkers reflecting DNA/RNA damage (8OHdG, 8OHG, and 5OHMeU), protein/amino acid oxidation (o-tyrosine, 3-chlorotyrosine, and 3-nitrotyrosine), and lipid oxidation (8-isoprostane, 4-hydroxy nonenal, and malondialdehyde [MDA]), as well as plasma total MDA and total protein carbonyl (TPC), with several nanoparticle exposure metrics in the same 19 healthy TPE operators. Plasma total MDA, urinary 5OHMeU, 3-chlorotyrosine, and 3-nitrotyrosine were positively, whereas o-tyrosine inversely and statistically significantly associated with PEPs exposure in multivariate models, after adjusting for age and urinary creatinine. Urinary 8OHdG, 8OHG, 5OHMeU, and total MDA in urine and plasma had group mean values higher than expected in healthy controls without PEPs exposure and comparable to those of workers experiencing low to moderate levels of oxidative stress (OS). The highest exposure group had OS biomarker values, most notably 8OHdG, 8OHG, and total MDA, that compared to workers exposed to welding fumes and titanium dioxide. Particle number concentration was the most sensitive and robust exposure metric. A combination of nanoparticle number concentration and OS potential of fresh aerosols is recommended for larger scale future studies.